Pakistan - North West Frontier Province Economic Report : Accelerating Growth and Improving Public Service Delivery in the NWFP : The Way Forward - World Bank (Washington, DC, 2012)
This report contends that the key to unleashing the North West Frontier Province's possibilities and to improving the lives of its citizens is strengthening the governance and policy environment in the province for both the private and the public sectors, and investing in the provinces' most valuable resource - its people. Reforms and efforts in the past few years have already started to translate into higher growth, improved incomes, and better living conditions for the citizens of the NWFP. This report outlines a strategy that builds on these successes and recommends policies to accelerate development in the province. The report recommends a comprehensive set of reforms and particularly advocates economic, fiscal, and institutional reform to improve outcomes for income growth, job creation, poverty reduction, and human development.